2014
DOI: 10.1089/jmf.2013.0071
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Attributes of Four Conventionally Extracted Medicinal Plants and Cytotoxic Evaluation of Their Extracts on Human Laryngeal Carcinoma (HEp2) Cells

Abstract: The bioactive composition and cytotoxic and antioxidative/prooxidative effects of four medicinal plants: yarrow (Achillea millefolium L.), hawthorn (Crataegus oxyacantha L.), ground ivy (Glechoma hederacea L.), and olive (Olea europea L.) on human laryngeal carcinoma cell line (HEp2) were investigated. Water extracts of these plants obtained by infusion, maceration, and decoction were characterized for their polyphenol content and antioxidant capacity. Based on the extraction efficiency of polyphenols, the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…There are no reported side effects following G. hederacea administration. However, one in vitro study showed that G. hederacea ethanol extract concentrations exceeding 100 µ g/dl are cytotoxic [ 160 ], and several studies now focus on the plant's ability to kill different types of cancer cells [ 162 ]. Due to its ability to target and kill cancerous cells, those extracts should also be included in preclinical screenings addressing pediatric cancerous cells (e.g., insulinomas being one of the most frequently encountered types of neuroendocrine pancreatic tumors [ 163 ]).…”
Section: Species Of the Lamiaceae Family With Potential Analgesic/mentioning
confidence: 99%
“…There are no reported side effects following G. hederacea administration. However, one in vitro study showed that G. hederacea ethanol extract concentrations exceeding 100 µ g/dl are cytotoxic [ 160 ], and several studies now focus on the plant's ability to kill different types of cancer cells [ 162 ]. Due to its ability to target and kill cancerous cells, those extracts should also be included in preclinical screenings addressing pediatric cancerous cells (e.g., insulinomas being one of the most frequently encountered types of neuroendocrine pancreatic tumors [ 163 ]).…”
Section: Species Of the Lamiaceae Family With Potential Analgesic/mentioning
confidence: 99%
“…Cytotoxicity of nettle extract was determined spectrophotometrically by the neutral red (NR) assay, as described by Belscak-Cvitanovic et al (2014). SW480 cells were seeded in wells (2·10 4 per well) of 96 well plates.…”
Section: Determination Of Biological Activity Of Nettle Extract In Vitromentioning
confidence: 99%
“…A slight increase of ROS formation was observed only after the tretament with 0.5x concentration of nettle extract, indicating the prooxidant activity, which was already established for non-H 2 O 2 pretreated cells. The prooxidant effect of lower concentrations of ground ivy and hawthorn extracts was also assessed by Belscak-Cvitanovic et al (2014). Since a correlation between the cytotoxicity and ROS formation was observed, meaning that higher nettle extract concentrations exert a high cytotoxicity and a decrease of ROS levels, the results indicate that different cellular responses are attributed for the observed effects.…”
Section: Comparison Of Different Extraction Techniques Of Nettlementioning
confidence: 99%
“…In Europe and North America, flowering tops (leaves and flowers) are used for their astringent, antispasmodic, cardiotonic, diuretic, hypotensive, vasodilative, sedative, antiatherosclerotic, and antihyperlipidemic properties [6,7,8,9,12,13,14,15,16,17,18,19,20,21,22,23]. Most of the experimental works published on Crataegus have focused on the extraction, quantification, and identification of phenolic compounds, flavonoids, and tannins to which the merit of these pharmacological effects is attributed [10,12,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. These bioactive principles are usually extracted in ethanol, methanol, or alcohol/water mixtures at different temperatures and extraction times by using various extraction modes, essentially Soxhlet [30,45,46,52,56,…”
Section: Introductionmentioning
confidence: 99%